Kinetic characterization of a cytoplasmic myosin motor domain expressed in Dictyostelium discoideum. - Ritchie, M D (1993)
A detailed kinetic study of the interaction of a recombinant myosin head fragment (MHF) of Dictyostelium discoideum with actin and adenine nucleotides has been made by using a combination of rapid-reaction, equilibrium, and fluorescence methods. MHF is equivalent in size to a proteolytic fragment of skeletal muscle myosin, subfragment 1 (S1), the simplest unit of myosin to retain enzymatic and functional activity. The results show that qualitatively the interactions of MHF with nucleotides and actin are the same as those of S1. Both bind to rabbit actin with the same affinity, although differences in the rate constants of their interactions with nucleotides in the presence and absence of actin occur. The rate of ATP binding to MHF and the subsequent cleavage step are significantly slower than the corresponding rates with S1. The dissociation of a fluorescent analog of ADP from MHF was 5-fold faster than from S1, while its rate of binding MHF was 3-fold slower, resulting in a weaker association equilibrium constant. The ATP-induced isomerization of the actoMHF complex was 10-fold slower than for actoS1, but the binding affinities of ADP for actoMHF and actoS1 were indistinguishable. The results suggest a different degree of coupling between the nucleotide and actin binding sites of MHF and S1 which may be a common feature of nonmuscle myosins. They also provide the basis for a study of specifically modified myosins with which one can probe the sites of interaction with nucleotides or actin, as well as functional motility.